El cine ecuatoriano: migrar o desaparecer. Caso de estudio de las plataformas de streaming Choloflix y Touché Premiere (Monográficos) - Zamora, Fredi (2022)
This article analyzes the way in which the development of national film production in the city of Quito is raised during the pandemic by studding the streaming platforms of national production Choloflix and Touché Premiere. We tried to understand if the pandemic meant a setback for national production or if it generated the innovation of new strategies of creation and distribution such as video streaming platforms with multimedia content. The results obtained lead us to conclude that the national cinema does not stop and that in the midst of an evident crisis it is generating new scenarios and virtual platforms, where the audiovisual producers have the challenge of providing solutions to the requirements of art with technological, conceptual and aesthetic proposals. It is important to think not only in the present but also in the cinema of the future that is now in cyberspace.